Others of My Kind Transatlantic Transgender Histories - Bakker, Alex (University of Calgary Press, 2020)
From the turn of the twentieth century to the 1950s, a group of transgender people on both sides of the Atlantic created communities that profoundly shaped the history and study of gender identity. By exchanging letters and pictures among themselves they established private networks of affirmation and trust, and by submitting their stories and photographs to medical journals and popular magazines they sought to educate both doctors and the public. Others of My Kind draws on archives in Europe and North America to tell the story of this remarkable transatlantic transgender community. This book uncovers threads of connection between Germany, the United States, and the Netherlands to discover the people who influenced the work of authorities like Magnus Hirschfeld, Harry Benjamin, and Alfred Kinsey not only with their clinical presentations, but also with their personal relationships. It explores the ethical and analytical challenges that come with the study of what was once private, secret, or unacceptable to say. With more than 180 colour and black and white illustrations, including many stunning, previously unpublished photographs, Others of My Kind celebrates the faces, lives, and personal networks of those who drove twentieth-century transgender history.